New compacton solutions of nonlinearly dispersive R(m, n) equations - İnç, Mustafa (Iop Publishing Ltd, 2006)
In this paper, we establish exact solutions for the R(m,n) equations by using an sn-cn method. As a result, abundant new compactons, i.e. solitons with the absence of infinite wings, new type of Jacobi elliptic function, solitary wave and periodic wave solutions, of this equation are obtained with minimal calculations. The properties of the R(m,n) equations are shown in figures.
Keywords: R(m, n) equation; compacton solution; soliton